Difusi Inovasi Aplikasi Quiver 3-D Berbasis Teknologi Augmented Reality Pada Lembaga Pendidikan Anak Usia Dini - Kisno K; Nia Fatmawati (Institut Agama Islam Negeri Madura, 2023)
This innovation diffusion research aims to disseminate innovative applications containing Augmented Reality (AR) technology in Early Childhood Education institutions through coloring activities in developing children's creativity. Because every child has talent and creativity that must be welcomed through various activities that can help their development. It is important for children in their learning environment to be given the opportunity to explore multi-media in order to realize the fertilization of their creative potential. Children's interest in digital devices can be used as a great opportunity for teachers in utilizing media and learning resources in early childhood education institutions. Augmented Reality (AR) technology content contained in the Q-3D Application in coloring activities provides an interesting offer by presenting virtual world visual images formed in 3-D animation into a real environment with the help of smartphones for images created and colored, so as to develop their creativity. In this innovation diffusion research, the descriptive analysis method is used with two approaches, namely: qualitative and quantitative. The data were obtained through three methods, namely: observation, interview, and documentation. Innovation diffusion research provides important findings that the level of adopter acceptance of the innovation of the Aaugmented Reality-based Quiver 3D app is very high and children's creativity is well developed.